First Journey by a Descriptive Review of Empirical Research on African Marital Relationships—Scientific Dissemination, Thematic Focus, and Methodology. Issue 3 (3rd April 2018) - Januário, Dulcineia; Narciso, Isabel; Vieira-Santos, Salomé; Fonseca, Gabriela; Relvas, Ana Paula
ABSTRACT: Family and marital research remains unrepresentative in African societies. The current study is a descriptive literature review of empirical research on African marital relationships published in peer-reviewed journals since the beginning of the 21st century. The aim of this study was to describe this body of research with regard to its methodology, main thematic foci, and scientific dissemination. Ninety studies published across 63 scientific journals were identified, with the majority of them using a quantitative and cross-sectional design. Marital satisfaction/quality and marital stability/instability were the two themes most frequently explored in the studies. Results also revealed that the number of published articles on the topic and the diversity of themes addressed have seen an increase over the years. Implications for the development of further research on African marital relationships are discussed.